A transdisciplinary mechanical skills curriculum for further education and training colleges in South Africa - Klinck, Albel Jacobus (University of the Free State, 2012)
South Africa has a low school completion rate of 40% (2002 - 2009), resulting from low-quality education as prime concern (Van der Berg et al, 2011: 1, 13). Consequently, this situation signifies a majority of learners being unsuccessful in mainstream education leaving them very little opportunities in "further" education. They (unsuccessful school leavers) have poor further education and employment prospects. Some of the unsuccessful school leavers resort to FET colleges for further education, but the programmes are not designed to address their specific educational needs. FET (mainstream) schools also refer poorly performing learners to FET colleges, oblivious of the high standard of vocational education programmes and associated entry requirements. Despite the fact that mathematics and physical science are compulsory for engineering studies (NC(V) and NATED), schools refer learners performing poorly in these subjects to engineering studies to "learn to work with their hands." However, these programmes are not specifically designed for skills training per se. The educational options unsuccessful school leavers have, do not make provision for their educational situation. They cannot learn effectively and this results in poor performance in mainstream school education and vocational education at FET colleges. Their ability to learn is further hampered by poor language, mathematics and science proficiencies fundamental to learning. South Africa does not have an educational component like the second chance schools in Great Britain and Europe to accommodate these learners. The European Commission initiated second chance schools for out-of-school unemployed (NEET) young people in 1995 and ran 12 pilot projects in 11 countries in Europe and England, from 1997 to 1999 (Chistolini, 2008:219). Greece, inter alia, established 48 second-chance schools across the country and reduced school dropout from 22,4% in 1995 to 15,9% in 2006. The situation of unsuccessful school leavers in South Africa, constituting an annual dropout of 60%, necessitates similar education to provide learners opportunities in further education and to give them hope. South Africa needs to improve learners' ability to learn and develop cognitive and psychomotor ability on a much larger scale than that of European second chance education. Simultaneously, school dropout must also be reduced by improving education on all levels of the system. Both of the mentioned aspects should be attempted by changing educational approach and presentation strategies based on sound psychological learning theories. Unsuccessful school leavers' education (the South African version of second chance education) should focus more on development of learning ability than the European counterpart does. Learners need todevelop capacity and shed their aversion to learning. Knowledge, fundamental to learning should be acquired. Unsuccessful school leavers' education requires an approach that initiates education with activities encouraging participation. Cognitive and psychomotor development, founded in these activities, will be more significant and meaningful to learners than subject-focused information (learning content). The attributes, educational foundation and predisposition of the learners should be taken into consideration in designing education for unsuccessful school leavers. What they bring to the learning opportunities is of paramount importance. Their previous experiences in education will have a major impact on how they will react and reflect on future exposure to educational activities. Replicating their previous experiences is a recipe for further failure. Their education should be based on experiences demonstrating to them their own importance in the processes of achieving the competences required. Strategies containing more encouraging activities that can lure learners into active involvement are indispensible. Classroom sessions, similar to those of their previous experiences of education, should be avoided. The unpropitious educational situation of unsuccessful school leavers can be addressed by providing education that can accommodate their specific educational needs. A curriculum based on transdisciplinary-integrated education with practicum-based presentation strategies will allow versatility that can accommodate differentiated development and qualifications. Transdisciplinaryintegrated education, based on practicum.methodology is inherently structured for skills development across the spectrum of a mechanical skills curriculum. Flexibility is further enhanced by constructivist fundamental learning theory denoting personal knowledge construction from personal perceptions and experiences.

Suid-Afrika het Onbaie lae skoolvoltooiingsyfer van 40% hoofsaaklik as gevolg van swak kwaliteit onderwys (Van der Berg, Burger, Burger, De Vos, Du Rand, Gustafsson, Moses, Shepherd, Taylor, Van Broekhuizen and Von Fintel, 2011:1,13). Uiteraard dui die situasie op Onmeerderheid leerders wat onsuksesvol is in hoofstroom onderwys met min geleenthede om verder onderwys te ontvang. Hulle vooruitsigte op verdere onderwys en werksgeleenthede is dus skraal. Sommige onsuksesvolle skoolverlaters wend hulle tot VOO kolleges vir verdere onderwys, maar die programme is nie ontwerp om hulle leerhindemisse te ondervang en aan hulle spesifieke onderwysbehoeftes te voldoen nie. VOO (hoofstroom) skole verwys swak presteerders na VOO kolleges onbewus van die hoë standaard van beroepsonderwys en gepaardgaande toelatingsvereistes. Ten spyte daarvan dat wiskunde en fisiese wetenskap verpligtend is vir ingenieursonderwys (NC(V) en NASOP), verwys skole leerders wat in hierdie vakke swak presteer, na ingenieurstudies "orn te leer om met hulle hande te werk." Hierdie programme is egter nie spesifiek ontwerp vir vaardigheidsontwikkeling as sodanig nie. Die onderwys opsies wat tot die beskikkingvan onsuksesvolle skoolverlaters is, maak nie voorsiening vir hulle besondere onderwyssituasie nie. Hulle kan nie effektief leer nie, gevolglik presteer hulle swak in hoofstroom skoolonderwys en VOO kollege beroepsonderwys. Hulle vermoë om te leer word verder benadeel deur Ongebrek aan wiskunde-, wetenskap- en taalvaardighede, grondliggend aan leervermoë. Suid-Afrika het nie Ononderwyskomponent, soortgelyk aan die "tweede-geleentheid skole" in Groot Brittanje en Europa, om hierdie leerders te akkommodeer nie. Die Europese Kommissie (European Commission) het in 1995 tweede-geleentheid skole geïnisieer en 12 loodsprojekte in II Europese lande van 1997 tot 1999 van stapel gestuur (Chistolini, 2008:219). Griekeland, onder andere, het 48 tweede-geleentheid skole reg oor die land gestig en terselfdertyd hulle skooluitvalsyfer van 22,4% in 1995 tot 15,9% in 2006 verminder. Die onsuksesvolle skoolverlaters se situasie in Suid-Afrika, met onuitvalsyfer van 60%, noodsaak soortgelyke onderwys om leerders Ongeleentheid in verdere onderwys, en dus hoop, te gee. Suid-Afrika moet op Onbaie groter skaal die leervermoë van leerders verbeter, kognitiewe en psigomotoriese vermoë ontwikkel as in die Europese tweede-geleentheid skole. Terselfdertyd moet skooluitval, met verbeterde onderwys op alle vlakke van die skoolstelsel, verminder word. Daar behoort gepoog te word om beide aspekte, hierbo vermeld, te verwesenlik deur die onderwysbenadering en aanbiedingstrategieë, gegrond op psigologiese leerteorieë, te wysig. In onderwys vir onsuksesvolle skoolverlaters (die Suid-Afrikaanse weergawe van tweede-geleentheid skole) moet daar meer gefokus word op leervermoë as in die Europese weergawe. Leerders moet leervermoë ontwikkel en hulle renons in leeraktiwiteite afskud. Kennis, grondliggend aan leervermoë, moet verwerf word. Onderwys vir onsuksesvolle skoolverlaters vereis 'n ander onderrigbenadering met aanvangsaktiwiteite wat deelname aanmoedig. Kognitiewe en psigomotoriese ontwikkeling wat op sulke aktiwiteite gegrond is, sal meer beduidend en sinvol vir die leerders wees as vakgerigte inligting (leerinhoud). Onderwys vir onsuksesvolle skoolverlaters behoort ontwerp te word met die hoedanighede en ingesteldheid van die leerders in oorweging. Wat hulle tot die leergeleentheid toevoeg, is van kardinale belang. Hulle vorige ervaring in onderwys sal 'n groot uitwerking hê op hulle reaksie op en weergawe van toekomstige blootstelling aan onderwys aktiwiteite. Navolging van hulle vorige ervarings is gedoem tot mislukking. Hulle onderwys moet gegrond word op ondervinding waarin hulle bewus sal word van hulle eie waarde in die prosesse om bevoegdheid te bereik. Strategieë wat aansporende aktiwiteite insluit en leerders tot deelname inspireer, is onontbeerlik. Klaskamer sessies, soortgelyk aan hulle vorige ervarings van onderwys, behoort vermy te word. Die ongunstige onderwyssituasie waarin onsuksesvolle skoolverlaters hulle bevind, kan aangepak word met onderwys wat hulle besondere onderwysbehoeftes kan bevredig. 'n Kurrikulum wat op transdissiplinêr geïntegreerde onderwys gegrond is, met praktikum-gegronde aanbiedings, bied veelsydigheid wat gedifferensieerde ontwikkeling en kwalifikasies moontlik maak. Transdissiplinêr geïntegreerde onderwys, gegrond op praktikum-metodologie is inherent gestruktureer vir vaardigheidsontwikkeling oor die spektrum van 'n meganiese vaardigheidskurrikulum. Aanpasbaarheid word verder bevorder deur die konstruktivistiese grondteorie wat persoonlike kennisbou uit eie persepsies en ervarings behels.
Thesis (Ph.D. (School of Mathematics, Natural Sciences and Technology Education))--University of the Free State, 2012
Keywords: Learning; Constructivism; Transdisciplinary; Practicum; Knowledge integration; Differentiated development; Universities and colleges -- Curricula -- South Africa; Curriculum change -- South Africa; Curriculum planning -- South Africa; Education, Higher -- Curricula -- South Africa; Constructivism (Education) -- South Africa; High school dropouts -- South Africa